Effect of the Diabetic Nephropathy Aggravation Prevention Program on medical visit behavior in individuals under the municipal national health insurance - Ikeda, Asuka; Fujii, Makoto; Ohno, Yuko; Godai, Kayo; Li, Yaya; Nakamura, Yuko; Yabe, Daisuke; Tsushita, Kazuyo; Kashihara, Naoki; Kamide, Kei; Kabayama, Mai (Journal of diabetes investigation, 2023)
ABSTRACT Aims/Introduction We aimed to clarify the effectiveness of the Diabetic Nephropathy Aggravation Prevention Program in Japan by comparing the diabetes‐related medical visit behavior of individuals under the municipal national health insurance according to insurers' effort levels. Materials and Methods We assessed changes in medical visit behavior according to insurers' effort levels, “Full Efforts,” “Some Efforts” and “No Effort,” using longitudinal data from the National Database of Health Insurance Claims and Specific Health Checkups before 2015 and after 2018 regarding the national health insurance programs in Japan. We analyzed the effect of the Diabetic Nephropathy Aggravation Prevention Program using a generalized linear mixed model for 208,388 participants with diabetes. Results The additive effect on medical visit behavior was significantly higher for insurers with “Full Efforts” than for those with “No Effort;” the coefficient (log odds ratio) was 0.159 (95% confidence interval 0.063–0.256). The additive effects on medical visit behavior sizes for the people with hemoglobin A1c ≥7.0%, positive urinary protein and systolic blood pressure ≥140 mmHg were 0.508, 0.402 and 0.232, respectively, which were larger than the overall effect size (0.159) for insurers with “Full Efforts.” Conclusions Our findings showed that insurer efforts had an additive effect on the increase in the number of medical visits, suggesting that this national program could reduce the number of end‐stage renal failures or dialysis in Japan. We present novel findings on the effects of insurer efforts on medical visit behavior in the Diabetic Nephropathy Aggravation Prevention Program; we showed that insurer efforts actively encouraged patients to undergo medical visits.